High impact of PGPR on biostatistic of Aphis craccivora (Hemiptera: Aphididae) on yardlong bean - Hermanu Triwidodo; Listihani LISTIHANI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Triwidodo H, Listihani. 2020. High impact of PGPR on biostatistic of Aphis craccivora (Hemiptera: Aphididae) on yardlong bean. Biodiversitas 21: 4016-4021. Plant growth-promoting rhizobacteria (PGPR) are root colonizing bacteria that live and develop near plant roots, which boost plant growth and act as antagonist agents. This research is aimed to asses the effect of PGPR on biostatistics of Aphis craccivora Koch on yardlong bean (Vigna unguiculata subsp. sesquipedalis). The research was conducted at WiSH Laboratory in Bogor, Indonesia, by tested PGPR  mixture of Rhizobium, Bacillus polymyxa, and Pseudomonas fluorescens. The research discovered that the application with seed treatment and watered of PGPR affects the biology of Aphis craccivora in terms of lengthening its stadia of second instar nymph, lengthening its life cycle, and declining its fecundity. The application of PGPR also affects the biostatistics of Aphis craccivora. PGPR applied plants have a gross reproduction rate (GRR), net reproduction rate (Ro) and intrinsic increase rate (r) of Aphis craccivora that are lower than control. PGPR could slower the doubled time (DT) of Aphis craccivora to become lengthier than control. PGPR could improve plant growth: it could increase the number and length of roots, number of root nodules, plant height, number of leaves, as well as length and density of trichome.